The history of Trombones de Costa Rica. Its life story as told by its main characters - Rodríguez Cambronero, Leonel (2022)
The article researches the musical history of Trombones de Costa Rica, a Costa Rican chamber music group with thirty years of national and international experience. The group was founded in 1991, by the chair of the trombone at the University of Costa Rica. The musical style stands out in chamber music and has been an inspiration for new groups, and also for the study and creation of songs composed mainly for this kind of music. This article highlights both its artistic achievements and its contribution to the dissemination and promotion of regional music, through the voice of its lead musicians. For this purpose, the life story methodology is applied (Thomas & Znaniecki, 1972). The self-stories of the lead musicians explains to the reader how the group was created, and how it has developed since then through the four generations. It also shows the role of each of its members over thirty years and the contributions of the group in the musical history of Costa Rica. It is an informative and experiential document that demonstrates the joint work of institutions, schools, and human beings in strengthening the Costa Rican musical culture.